The locality of Trapa natans L. within the region of Międzyodrze – dangers and protection perspective (the Lower Oder Valley, West Pomerania) - Kowalski, Wojciech W. A.; Wróbel, Mariola; Jurzyk-Nordlöw, Sylwia (Biodiversity: Research and Conservation, 2018)
Research on a critically endangered and protected population of Trapa natans was carried out during growing season in 2016 at the site located on the Obnica channel within the region of Międzyodrze. It is a location that is close to the one indicated in historical sources by Winkelmann over 120 years ago. The post-war research did not confirm presence of this species within the region of Międzyodrze despite favourable biological conditions. The sites were declared relict and documented only in stratigraphy of peat deposits, detritus gyttja and bottom mineral sediments. Recently, an assessment of the population and habitat status were carried out. The appropriate indicators of the species status were examined according to the methodology of Chief Inspectorate of Environmental Protection. The floristic composition of Trapetum natantis association patches found within the researched site were analysed, reed bed associations belonging to the class of Phragmitetea and plant communities of pleustophytes, nymphaeids and elodeids belonging to the class Potametea and Lemnetea were recognised in the contact zone. On the basis of the collected data, particular attention was paid to the relevance of Trapa natans monitoring at the site located on the Obnica channel within the Międzyodrze region due to its indicative character. The conservation status of the population could be influenced by the change of water trophy within Międzyodrze channels caused by different forms of anthropopressure, including commercial use of this water body, hydromeliorative works, changes that are due to the progressive succession of water plants and reeds, which slow down the water flow rate within the area of Międzyodrze, favour accumulation of organic matter and increase of water trophy as well as fluctuations of surface water thermal activity caused by changing weather conditions.